High and low body mass index increases the risk of short-term postoperative complications following total shoulder arthroplasty - Salvatore Capotosto, MD; Matthew Kim, MD; Kenny Ling, MD; Alireza Nazemi, MD; Ryan Tantone, MD; Elizabeth Wang, MD; David E. Komatsu, PhD; Edward D. Wang, MD (JSES International)
Background: Several studies have investigated the impact of body mass index (BMI) on total shoulder arthroplasty (TSA) outcomes and reported contrasting results. Therefore, this study aims to better understand the impact of BMI on 30-day post-TSA outcomes by performing a comprehensive risk stratification based on BMI using a large national database. Methods: All patients undergoing TSA, both anatomic and reverse, between 2015 and 2019 were queried from the American College of Surgeons National Surgical Quality Improvement Program database. The study population was stratified into 6 cohorts: BMI < 18.5 kg/m2 (underweight), BMI of 18.5-24.9 kg/m2 (reference cohort), BMI of 25.0-29.9 kg/m2 (overweight), BMI of 30.0-39.9 kg/m2 (obese), BMI of 40.0-49.9 kg/m2 (morbidly obese), and BMI ≥ 50.0 kg/m2 (super-morbidly obese). Postoperative complications within 30 days of surgery were collected. Multivariate logistic regression was conducted to investigate the association between BMI values and postoperative complications. Additionally, to facilitate a direct comparison with existing literature, and further validate our study methodology, a subgroup analysis with multivariate logistic regression was made comparing 2 groups: BMIs > 30 kg/m2 and BMIs < 30 kg/m2. Odds ratios (ORs) were reported with a 95% confidence interval. The level of statistical significance was set at P < .05. The analyses were conducted using SPSS 26.0. Results: A total of 22,542 patients undergoing TSA between 2015 and 2019 were reported in the database. Of these, 410 patients did not have reported BMIs, leaving 22,132 patients for the analysis (1.8% attrition bias). The underweight cohort had a greater likelihood of mortality (OR, 6.184; P = .008) and nonhome discharge (OR, 1.824; P = .008). The morbidly obese cohort had a greater likelihood of developing wound infections (OR, 5.254; P < .002). The super-morbidly obese cohort presented a greater likelihood of developing wound infections (OR, 13.431; P = .002) and nonhome discharge (OR, 1.525; P = .035). Conclusion: Patients with BMI less than 18 and more than 40 were associated with an increased incidence of 30-day postoperative TSA complications such as wound infection, nonhome discharge, and mortality. Based on these findings, preoperative risk stratification based on BMI remains an important part of elective surgery.